2013
DOI: 10.1371/journal.pone.0054603
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Genotyping by Sequencing (GBS) Approach Offering Increased Versatility and Efficiency of SNP Discovery and Genotyping

Abstract: Highly parallel SNP genotyping platforms have been developed for some important crop species, but these platforms typically carry a high cost per sample for first-time or small-scale users. In contrast, recently developed genotyping by sequencing (GBS) approaches offer a highly cost effective alternative for simultaneous SNP discovery and genotyping. In the present investigation, we have explored the use of GBS in soybean. In addition to developing a novel analysis pipeline to call SNPs and indels from the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
376
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(390 citation statements)
references
References 19 publications
7
376
6
1
Order By: Relevance
“…This was due to the high number of repetitive sequences in the genome which made tag alignments problematic (Treangen and Salzberg 2012). However, when compared with other GBS studies, the number of identified SNPs after filtering in this study (9535) was similar to the numbers reported in Rubus idaeus (9143) and soybean (10,120) (Ward et al 2013;Sonah et al 2013).…”
Section: Gbs and Snp Identificationsupporting
confidence: 68%
See 1 more Smart Citation
“…This was due to the high number of repetitive sequences in the genome which made tag alignments problematic (Treangen and Salzberg 2012). However, when compared with other GBS studies, the number of identified SNPs after filtering in this study (9535) was similar to the numbers reported in Rubus idaeus (9143) and soybean (10,120) (Ward et al 2013;Sonah et al 2013).…”
Section: Gbs and Snp Identificationsupporting
confidence: 68%
“…The average frequency of sunflower SNPs identified in this study was 72 kb/SNP (1 SNP every 72 kb); this is higher than soybean (100 kb/SNP) (Sonah et al 2013) and much lower than the frequency identified in oil palm (1 SNP in 0.665 kb) (Pootakham et al 2015). Again, the higher frequency of SNPs in oil palm could reflect the higher number of reads and higher coverage of the oil palm alignment (88 %).…”
Section: Gbs and Snp Identificationcontrasting
confidence: 53%
“…DArTseq combines genome complexity reduction methods and next-generation sequencing platforms (Courtois et al, 2013;Cruz et al, 2013;Raman et al, 2014;Kilian et al, 2016). Therefore, DArTseq represents a new implementation of sequencing of complexity-reduced representations (Huang et al, 2014) and more recent applications of this concept on the nextgeneration sequencing platforms (Sonah et al, 2013;Bastien et al, 2014).…”
Section: Snp Discovery By Dartseqmentioning
confidence: 99%
“…The use of other enzyme combinations could circumvent this problem by altering the library construction [20,28]. In addition, the accuracy of base calling in complex polyploids and heterozygous individuals, of which there are several examples within the root and tuber staple crops of Africa, can also be problematic.…”
Section: Ngs-based Genotyping and Marker Analysismentioning
confidence: 99%
“…Sequencing DNA and RNA has become so cheap and so vast that NGS is now a basic technology for many fields of research in medicine, basic research, as well as research in agriculture. In agricultural research, NGS is applied in whole-genome sequencing (WGS), whole-genome re-sequencing (WGRS), transcriptomics, metagenomics, and reduced representation sequencing for high-throughput SNP genotyping [15,21,28,29,49]. A genome sequence becomes only useful for biological applications when the genome is annotated and genes are described and their functions revealed [50].…”
Section: Bioinformatics and Databasementioning
confidence: 99%